Improving Students’ Learning Activities in Physics Science Using the Inductive Thinking Model - Syafii, Khairul; Rahman, Alim Shafiyyur; Basyiruddin, Basil (Journal of Education and Social Science, 2024)
This research aims to determine the Biology Science learning activities of Class X students at MTs. Addinul Qayyim Kapek uses the Inductive Thinking Model. This type of research is Classroom Action Research (CAR) with the data collection tool used is teacher and student activity observation sheets. Based on data analysis, the results obtained in cycle I, Meeting I, teacher activity score were 59.37% in the quite active category. The action was continued until the second cycle. At the second meeting of cycle II the teacher activity score was 78.12% in the active category. Cycle I Meeting I student activity score was 47.05% in the quite active category. The action was continued until the second cycle. At the second meeting of cycle II, the student activity score was 64.70% in the active category. From these results it can be concluded that the research action was successful because it could increase students' biology learning activities using the Inductive Thinking Learning Model.